Progressive leadership : challenging the theory of the firm in the 21st century - Park, Greg (Emerald Publishing Limited, 2022)
Progressive Leadership addresses the diminishing and increasingly dysfunctional contribution of firm leadership in the operational effectiveness, performance, and survival of the firm in the business context of the twenty-first century. Leadership has effectively lost its licence to lead. Progressive Leadership investigates the purpose, principles, perspectives, and priorities of the prevailing theory of the firm which directs and colours the process of leadership in terms of operational decision making and interaction with other enfranchised investors. For leadership to optimally fulfil its role and responsibilities a new theory of the firm is required, one which considers and rewards a wider group of enfranchised 'investors' to optimally leverage their assets for the benefit of the firm. This will only successfully be achieved by leaders taking a more front of mind psychological approach, better anticipating the reactions and responses of the key asset of the firm, the knowledge and innovation laden 'investors'. The book profiles a number of substantial firms which have successfully recognised the benefits of prioritising the principles of enfranchised investors and a psychological approach to leadership and concludes with an action plan as a template for existing and aspiring leaders to apply the purpose, principles, and priorities of the progressive leadership logic within their own firm.